Thermal rejuvenation in metallic glasses. Issue 1 (31st December 2017) - Saida, Junji; Yamada, Rui; Wakeda, Masato; Ogata, Shigenobu
Abstract: Structural rejuvenation in metallic glasses by a thermal process (i.e. through recovery annealing) was investigated experimentally and theoretically for various alloy compositions. An increase in the potential energy, a decrease in the density, and a change in the local structure as well as mechanical softening were observed after thermal rejuvenation. Two parameters, one related to the annealing temperature, T a / T g, and the other related to the cooling rate during the recovery annealing process, V c / V i, were proposed to evaluate the rejuvenation phenomena. A rejuvenation map was constructed using these two parameters. Since the thermal history of metallic glasses is reset above 1.2 T g, accompanied by a change in the local structure, it is essential that the condition of T a / T g  ≥ 1.2 is satisfied during annealing. The glassy structure transforms into a more disordered state with the decomposition of icosahedral short-range order within this temperature range. Therefore, a new glassy structure (rejuvenation) depending on the subsequent quenching rate is generated. Partial rejuvenation also occurs in a Zr55 Al10 Ni5 Cu30 bulk metallic glass when annealing is performed at a low temperature ( T a / T g ~ 1.07) followed by rapid cooling. This behavior probably originates from disordering in the weakly bonded (loosely packed) region. This study provides a novel approach to improving the mechanical properties of metallic glasses by controlling their glassy structure. Abstract :